Penentuan Jumlah Pesanan Bahan Baku Pada Sistem Persediaan Backorder Di PT ABC - Tombak Gapura Bhagya (Universitas Insan Cendekia Mandiri, 2019)
Inventory Control is part of production planning that needs to be considered in more detail. In the case of raw material inventory, if there is a delay or a vacancy in the stock, then the worst risk is termination of the production process. In order to avoid these conditions, an inventory model is made that includes backorder elements, with the hope that there will be no shortage of raw materials, even if it does, then there will be a substantial penalty. In the case of PT ABC, it resulted in inventory costs is Rp 1.739.774.271,00and this reiterates that the inventory needs to be managed well because of the large value that must be managed